Immune Escape and Immune Checkpoint-associated Therapies in the Tumour Microenvironment of Head and Neck Squamous Cell Carcinoma - Yang, Qinzhi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Head and neck squamous cell carcinoma (HNSCC) comprises a prevalent category of malignant neoplasms that present as oropharyngeal, oral cavity, laryngopharyngeal, hypopharyngeal, and laryngeal cancers. Each year, close to a million people around the globe find themselves grappling with these fierce and relentless cancers. Addressing HNSCC often requires a multifaceted approach, ranging from surgical intervention and radiation to chemotherapy, immunotherapy, or a blend of these treatments. Nonetheless, the five-year survival rate for HNSCC persists at fifty percent overall and has not exhibited substantial improvement in recent years. Prior research has demonstrated that the tumor microenvironment (TME) significantly influences recurrence, metastasis, and drug resistancein individuals with HNSCC. This review outlines the roles of both anti-tumor and pro-tumor immune cells, as well as the extracellular components of the tumor microenvironment (TME) in head and neck squamous cell carcinoma (HNSCC).The discussion encompasses classical immunotherapies for HNSCC, the molecular pathogenesis of HNSCC, the tumor microenvironment in HNSCC, and the mechanisms through which HNSCC cells evade immune surveillance. The paper highlights several clinical trials that focus on using CTLA-4 inhibitors alongside combination therapies involving programmed cell death protein 1 (PD-1) and its ligand, PD-L1. As well as looking forward to some potential therapeutic approaches in clinical care that are expected to provide new strategies for clinical treatment.